LEGAL CERTAINTY OVER ASSET OWNERSHIP IN SUKUK IJARAH INSTRUMENTS IN INDONESIA - Imron (QANUN: Journal of Islamic Laws and Studies, 2026)
Sukuk Ijarah is a rapidly growing Islamic financial instrument in Indonesia and globally, offering relatively stable returns while complying with Sharia principles. Normatively, its issuance is regulated under Law No. 19 of 2008 on State Sharia Securities (SBSN), the OJK regulations on the Islamic capital market, and DSN-MUI Fatwas No. 41/2008 and 69/2008. However, market practices show a dominance of asset-based structures, where investors only acquire rights to the economic benefits of assets through a Special Purpose Vehicle (SPV), rather than physical ownership, making sukuk potentially unsecured in case of default. This raises two main issues: legal certainty and investor protection, and compliance with ownership and risk principles. This study employs normative legal research with conceptual and statutory approaches, using primary and secondary legal materials, analyzed through descriptive qualitative and comparative methods. Based on Hans Kelsen’s and Gustav Radbruch’s theories, Sukuk Ijarah normatively satisfies legal certainty, justice, and utility, as ownership is limited to asset benefits while default risk remains an inherent part of investment. Therefore, investors must understand the characteristic of beneficial ownership and the inherent risks of Sukuk Ijarah, including the legal and economic consequences if the issuer becomes insolvent.